Role of Intravenous Dexmedetomidine Premedication on Intra-operative Hemodynamics and PONV in Laparoscopic Cholecystectomy - Jabbar, Abdul; Hasan, M; Rahman, M; Alam, Shafiul; Tahsim, Naima; Mondal, Subrata Kumar (Journal of the Bangladesh Society of Anaesthesiologists, 2018)
Background: Laparoscopic cholecystectomy is a gold standard surgical procedure for gallbladderoperation. It causes altered hemodynamic responses due to pneumoperitoneum and surgical procedurealso causes high incidence of postoperative nausea & vomiting (PONV). Dexmedetomidine has beenshown to reduce intraoperative hemodynamic instability and PONV. Objective: This study was designed to evaluate the efficacy of intravenous dexmedetomidine premedicationfor attenuation of hemodynamic responses associated with pneumoperitoneum & its effect on postoperativenausea &vomiting. Methods: Sixty adult patients of ASA physical status I & II scheduled for elective laparoscopiccholecystectomy were enlisted for a prospective randomized double blind study. They were selectedrandomized into two equal groups, thirty in each group. Group A received 0.9% normal saline 100 ml &Group B received dexmedetomidine (100μgm) in 100 ml 0.9% normal saline intravenously for 10 minutesbefore induction of anaesthesia. Pulse rate, mean arterial pressure were recorded prior to induction, 2minutes after endotracheal intubation, before pneumoperitoneum,10 minutes & 20 minutes afterpneumoperitoneum, 10 minutes after release of carbon dioxide(CO2) & 10 minutes after extubation. Inpost anaesthetic care unit patient were observed on 2,6,12,24 hour for PONV. Results: Patients in Group B (dexmedetomidine) maintained greater hemodynamic stability compare toGroup A after intubation, during pneumoperitoneum and also extubation. Pulse rate & mean arterialpressure significantly varies in Group A compare with Group B at different times of intraoperative period(p <0.05). Postoperative nausea & vomiting was significantly less in Group B (dexmedetomidine). Conclusion: Premedication with intravenous dexmedetomidine (100 μgm) attenuates the hemodynamicresponses produced by pneumoperitoneum during laparoscopic cholecystectomy and also significantlyreduces nausea and vomiting. JBSA 2018; 31(1): 29-37